Innovation Of Sharia Financial And Banking Products In MSME Development - Mohammad Subkhan (Journal of Management, Economic, and Financial, 2023)
The innovation of financial products at the KHAS Kempek Micro Waqf Bank, Cirebon Regency is one of several sharia MFIs for community empowerment programs through the establishment of Sharia MFIs around Islamic boarding schools, which in its establishment were facilitated by the Financial Services Authority (OJK) and the Small Business Business Incubation Center ( PINBUK). This study aims to find out how to optimize the utilization of existing Islamic products in Micro Waqf Banks for Financial Innovation and Islamic Banking in MSME Development. Method study using a qualitative approach by design descriptive analytical . Source of data used is primary data sources from data obtained by observing and interviewing directly from the source, namely the Micro Waqf Bank KHAS Kempek Cirebon Regency as well as collecting documentation from books, articles, journals, internet and various other sources which are then processed and analyzed with stages of analysis that include data reduction, data display and verification and conclusion . Results from study shows that Islamic Finance and Banking Innovation of Micro Waqf Bank Kempek Kempek Cirebon Regency for Economic Empowerment of Micro Business Actors (MSMEs) around the Pesantren Environment is operating with sharia principles that are committed to tackling problems of poverty and inequality by providing access to capital for the productive poor or to micro business actors around Islamic boarding schools to improve their standard of living and help them with loans that are unsecured or collateralized and most importantly with a very low margin of 3% per year, by maximizing cash waqf funds in providing loans capital, coaching and evaluation. It was concluded that the Micro Waqf Bank KHAS Kempek Cirebon Regency had succeeded in empowering the economy of micro business actors around the Islamic boarding school with sharia principles